Determinação de contaminates inorgânicos em nanotubos de carbono por ICP-OES e ICP-MS - Krzyzaniak, Sindy Raquel (2016)
In this work, microwave-assisted wet digestion using the single reaction chamber (MAWD-SRC) and microwave-induced combustion (MIC) methods were investigated for the decomposition of carbon nanotubes (CNTs) and further determination of inorganic contaminants by inductively coupled plasma optical emission spectrometry (ICP-OES) and by inductively coupled plasma mass spectrometry (ICP-MS). Initially, the CNTs were decomposed by microwave-assisted wet digestion (MAWD) and the results obtained were considered as reference values. Parameters investigated for MAWD-SRC were the irradiation temperature (220 to 270 °C), the mass of CNT (25 to 300 mg) and the composition of digestion mixture (HNO3 and H2O2). Quantitative recoveries were obtained for Al, As, Ca, Cd, Co, Cr, Fe, La, Mg, Mn, Mo, Ni, Pb, V and Zn, using 275 mg of CNT, 6 mL of 14.4 mol L-1 HNO3 and 0.5 mL of 30% H2O2 with an irradiation program of 65 min. Using the optimized conditions, the results obtained after the decomposition of CNTs by MAWD-SRC, presented no statistical difference when compared with those obtained using the reference method (MAWD). The accuracy of MAWD-SRC method was also evaluated through the determination of some elements by neutron activation analysis (NAA) and also by high resolution continuum source graphite furnace atomic absorption spectrometry with direct solid sampling (DSS-HR-CS-GF AAS) and no statistical difference between the results were observed. In addition, the results obtained for a certified reference material (CRM) of SWCNT presented no difference in relation to the certified values. Parameters of MIC method, such as the mass of CNT (25 to 500 mg), the concentration of absorbing solutions (1, 4, 7 e 14.4 mol L-1 of HNO3), the acid mixture (HNO3+HCl in proportion 3+1 and 1+1) and the reflux time (5 to 15 min) were optimized. For quantitative recoveries of all analytes using MIC, 15 min of reflux using the acid mixture of HNO3+HCl (3+1) and decomposition of up to 100 mg of CNT were necessary. Using the optimized conditions, no statistical difference was observed between the results obtained by reference method (MAWD) and by DSS-HR-CS-GF AAS.